Effects of Website Attributes on Customer Satisfaction in Nepalese E-Tailing Business - Gaudel, Dibas; Sawagvudcharee, Ousanee (Nepalese Journal of Management Science and Research, 2019)
The study aims to investigate the effects of website attributes factor on customer satisfaction in e-tailing business of Nepal. The study identified that the website attributed to motivate e-consumers to shop online. The study argues that website security and website response has positive significant effect on customer satisfaction in Nepalese e-tailing business whereas there is no significant effect between the website structure, website personalization and website adequacy with customer satisfaction in Nepalese e-tailing business.